Results Taggings of Antarctic Whales - Mikhalev, Yu.A.; Kozachenko, L.M. (Український антарктичний журнал, 2012)
Methods of whale marking are described in historical order. Marks of different types are described, and their effectiveness is analyzed. Commercial whale migration maps in the Antarctic and nearby waters, based on mark return, are given. Perspectives of use of photo identification of whales, satellite radio marks and biopsy DNA analysis are given.